A signature-based classification of lung adenocarcinoma that stratifies tumor immunity - Zhang, Xun; Jiang, Dizhi; Li, Shunjia; Zhang, Xinyu; Zheng, Wendi; Cheng, Bo (Frontiers in Oncology, 2023)
Background: Immune-related subgroup classification in immune checkpoint blockade (ICB) therapy is largely inconclusive in lung adenocarcinoma (LUAD). Materials and Methods: First, the single sample Gene set Enrichment Analysis (ssGSEA) algorithm and K-means algorithm were used to identify immune-based subtypes for LUAD cohort based on the immunogenomic profiling of 29 immune signatures from the Cancer Genome Atlas (TCGA) database (n = 535). Second, we conducted a bioinformatics analysis on data to examine the prognostic and predictive value of immune-based subtypes. The survival analysis and further COX proportional hazards regression analysis were conducted in LUAD. Then, immune score, tumor-infiltrating immune cells (TIICs) and immune checkpoint expression of the three subtypes were analyzed respectively. In the end, the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) of the differentially expressed genes (DEGs) between 3 immune-based subtypes were analyzed for functional enrichment pathways. Result: A total of three immune-based subtypes with different immune signatures were identified for LUAD. We identified three LUAD subtypes that named cluster 1 (C1), cluster 2 (C2) and cluster 3 (C3). Patients in cluster 3 had higher stromal, immune, and ESTIMATE scores, while cluster 1 was the opposite. Cases in cluster 1 showed an enrichment of Macrophages M0 and activation of Dendritic cell, while in cluster 3 tumors were enriched in CD8+ T cell, activation of CD memory T cells and Macrophages M1. Cluster 3 was characterized by greater immune cell infiltration, as well as better survival prognosis compared to the other subtypes. What’s more, patients in cluster 3 had higher expression levels of immune checkpoint such as PD-L1, PD1, CTLA4, LAG3, IDO1 and HAVCR2. TMB score of clusters had no significantly statistical differences. Furthermore, we identified that immune-related pathways were enriched in cluster 3. Conclusion: LUAD subtypes that are based on immune signatures may contribute to the development of novel therapeutic treatment strategies for LUAD.